PERTANGGUNGJAWABAN TERHADAP PERBUATAN MELAWAN HUKUM INGKAR JANJI MENGAWINI (KUHPerdata DAN YURISPRUDENSI MA No. 3191 K/Pdt/1984) - Yuliana, Anisa; Aloysius, Sukardan; Mauritsius, Darius (Petitum Law Journal, 2025)
Legal responsibility for breaking a promise to marry is by filing a civil lawsuit for an unlawful act to the district court where the defendant is domiciled, then waiting for the results of the trial in the district court. And from the results of the trial a court decision will emerge which can be in the form of the lawsuit being granted, the lawsuit being rejected or the lawsuit not being accepted. And the limits of liability in the unlawful act of breaking a promise to marry are limited to what is stated in the Decree and the Defendant's movable and immovable assets. In this regard, the aim of this research is to find out the legal responsibility for breaking a promise to marry and the limits of liability. The research method used in this research is Normative Law. Normative research uses library materials as a source of research data, or also called library research, a method used to collect data from various literature. The results of this research are to find out the intended purpose, namely that there is still a lack of accountability for the act of refusing to marry and there is no clear accountability for the perpetrator of the default.